Installation of -SO2F groups onto primary amides - Liu, Jing; Wang, Shi-Meng; Alharbi, Njud S.; Qin, Hua-Li (Beilstein Journal of Organic Chemistry, 2019)
A protocol of SO2F2-mediated installation of sulfonyl fluoride onto primary amides has been developed providing a new portal to sulfur(VI) fluoride exchange (SuFEx) click chemistry. The generated molecules contain pharmaceutically important amide and -SO2F moieties for application in the discovery of new therapeutics.
Keywords: N-fluorosulfonyl amides; primary amides; sulfuryl fluoride (SO2F2)

(untitled) - Dong, J.; Krasnova, L.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2014)
Angew. Chem. 2014, 126, 9584–9602. doi:10.1002/ange.201309399

(untitled) - Wang, H.; Zhou, F.; Ren, G.; Zheng, Q.; Chen, H.; Gao, B.; Klivansky, L.; Liu, Y.; Wu, B.; Xu, Q.; Lu, J.; Sharpless, K. B.; et al. (Angew. Chem., Int. Ed., 2017)
Angew. Chem. 2017, 129, 11355–11360. doi:10.1002/ange.201701160

(untitled) - Gao, B.; Zhang, L.; Zheng, Q.; Zhou, F.; Klivansky, L. M.; Lu, J.; Liu, Y.; Dong, J.; Wu, P.; Sharpless, K. B. (Nat. Chem., 2017)

(untitled) - Liu, Z.; Li, J.; Li, S.; Li, G.; Sharpless, K. B.; Wu, P. (J. Am. Chem. Soc., 2018)

(untitled) - Qin, H.-L.; Zheng, Q.; Bare, G. A. L.; Wu, P.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2016)
Angew. Chem. 2016, 128, 14361–14364. doi:10.1002/ange.201608807

(untitled) - Zha, G.-F.; Zheng, Q.; Leng, J.; Wu, P.; Qin, H.-L.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2017)
Angew. Chem. 2017, 129, 4927–4930. doi:10.1002/ange.201701162

(untitled) - Schimler, S. D.; Cismesia, M. A.; Hanley, P. S.; Froese, R. D. J.; Jansma, M. J.; Bland, D. C.; Sanford, M. S. (J. Am. Chem. Soc., 2017)

(untitled) - Epifanov, M.; Foth, P. J.; Gu, F.; Barrillon, C.; Kanani, S. S.; Higman, C. S.; Hein, J. E.; Sammis, G. M. (J. Am. Chem. Soc., 2018)

(untitled) - Liang, Q.; Xing, P.; Huang, Z.; Dong, J.; Sharpless, K. B.; Li, X.; Jiang, B. (Org. Lett., 2015)

(untitled) - Zhang, E.; Tang, J.; Li, S.; Wu, P.; Moses, J. E.; Sharpless, K. B. (Chem. – Eur. J., 2016)

(untitled) - Fang, W.-Y.; Leng, J.; Qin, H.-L. (Chem. – Asian J., 2017)

(untitled) - Wang, X.-Y.; Leng, J.; Wang, S.-M.; Asiri, A. M.; Marwani, H. M.; Qin, H.-L. (Tetrahedron Lett., 2017)

(untitled) - Fang, W.-Y.; Huang, Y.-M.; Leng, J.; Qin, H.-L. (Asian J. Org. Chem., 2018)

(untitled) - Revathi, L.; Ravindar, L.; Leng, J.; Rakesh, K. P.; Qin, H.-L. (Asian J. Org. Chem., 2018)

(untitled) - Zhao, C.; Fang, W.-Y.; Rakesh, K. P.; Qin, H.-L. (Org. Chem. Front., 2018)

(untitled) - Zha, G.-F.; Fang, W.-Y.; Li, Y.-G.; Leng, J.; Chen, X.; Qin, H.-L. (J. Am. Chem. Soc., 2018)

(untitled) - Zhao, C.; Zha, G.-F.; Fang, W.-Y.; Rakesh, K. P.; Qin, H.-L. (Eur. J. Org. Chem., 2019)

(untitled) - Zhang, X.; Rakesh, K. P.; Qin, H.-L. (Chem. Commun., 2019)

(untitled) - Wang, S.-M.; Zhao, C.; Zhang, X.; Qin, H.-L. (Org. Biomol. Chem., 2019)

(untitled) - Narayanan, A.; Jones, L. H. (Chem. Sci., 2015)

(untitled) - Moss, D. E.; Berlanga, P.; Hagan, M. M.; Sandoval, H.; Ishida, C. (Alzheimer Dis. Assoc. Disord., 1999)

(untitled) - Kitz, R.; Wilson, I. B. (J. Biol. Chem., 1962)

(untitled) - Kumar, A. A.; Mangum, J. H.; Blankenship, D. T.; Freisheim, J. H. (J. Biol. Chem., 1981)

(untitled) - Esch, F. S.; Allison, W. S. (J. Biol. Chem., 1978)

(untitled) - Hanley, P. S.; Clark, T. P.; Krasovskiy, A. L.; Ober, M. S.; O’Brien, J. P.; Staton, T. S. (ACS Catal., 2016)

(untitled) - Mortenson, D. E.; Brighty, G. J.; Plate, L.; Bare, G.; Chen, W.; Li, S.; Wang, H.; Cravatt, B. F.; Forli, S.; Powers, E. T.; Sharpless, K. B.; Wilson, I. A.; et al. (J. Am. Chem. Soc., 2018)

(untitled) - Chen, W.; Dong, J.; Plate, L.; Mortenson, D. E.; Brighty, G. J.; Li, S.; Liu, Y.; Galmozzi, A.; Lee, P. S.; Hulce, J. J.; Cravatt, B. F.; Saez, E.; et al. (J. Am. Chem. Soc., 2016)

(untitled) - Gilles, P.; Veryser, C.; Vangrunderbeeck, S.; Ceusters, S.; Van Meervelt, L.; De Borggraeve, W. M. (J. Org. Chem., 2019)

(untitled) - Sulbaek Andersen, M. P.; Blake, D. R.; Rowland, F. S.; Hurley, M. D.; Wallington, T. J. (Environ. Sci. Technol., 2009)

(untitled) - Guo, T.; Meng, G.; Zhan, X.; Yang, Q.; Ma, T.; Xu, L.; Sharpless, K. B.; Dong, J. (Angew. Chem., Int. Ed., 2018)
Angew. Chem. 2018, 130, 2635–2640. doi:10.1002/ange.201712429

(untitled) - Spillane, W.; Malaubier, J.-B. (Chem. Rev., 2014)

The Amide Linkage: Structural Significance in Chemistry, Biochemistry and Materials Science - Greenberg, A.; Breneman, C. M.; Liebman, J. F. (Wiley-Interscience, 2000)

The World of Peptides: A Brief History of Peptide Chemistry - Wieland, T.; Bodanszky, M. (Springer-Verlag, 1991)

(untitled) - de Figueiredo, R. M.; Suppo, J.-S.; Campagne, J.-M. (Chem. Rev., 2016)

(untitled) - Crespo, L.; Sanclimens, G.; Pons, M.; Giralt, E.; Royo, M.; Albericio, F. (Chem. Rev., 2005)

(untitled) - Roesky, H. W.; Giere, H.-H. (Chem. Ber., 1969)

(untitled) - Clauβ, K.; Friedrich, H.-J.; Jensen, H. (Justus Liebigs Ann. Chem., 1974)

Ger. Pat. Appl. - Pietsch, H.; Clauss, K.; Jensen, H.; Schmidt, E. (Verfahren Zur Herstellung Von Acetoacetamid-N-sulfofluorid, 1976)

U.S. Patent - Linkies, A.; Reuschling, D. (Process for preparing crystalline salts of acetoacetamide-N-sulfofluoride, 1986)

(untitled) - Appel, R.; Rittersbacher, H. (Chem. Ber., 1964)

(untitled) - Appel, R.; Montenarh, M. (Chem. Ber., 1976)

(untitled) - Beran, M.; Příhoda, J.; Taraba, J. (Polyhedron, 2010)

(untitled) - Liu, C.; Shi, S.; Liu, Y.; Liu, R.; Lalancette, R.; Szostak, R.; Szostak, M. (Org. Lett., 2018)